Aplicação de regulador vegetal e poda nas relações fisiológicas na produção do tomateiro - Spadoni, Thais Botamede [UNESP] (2015)
Two experiments were conducted, the first with the aim to evaluate the best stage for performing foliar application of the mixture of auxin (Ax), cytokinins (CK) and gibberellins (GA), in particular tomato (Solanum lycopersicum L.), using a dose of 0,20% of the product. The second experiment in order to evaluate the effect of Belgian pruning and the influence of mixing auxin (Ax), cytokinin (CK) and gibberellic acid (GA) in the development and metabolism of plants. The first experiment was conducted in the experimental area of the Faculty of Agricultural Sciences at the Universidade Estadual Paulista-UNESP, in São Manuel. The experimental design was randomized blocks with 16 treatments, four replications: T1:Control; T2: Before Transplant; T3: Before Transplant + Rooting; T4: Before Transplant + Rooting + Sprouting; T5: Before Transplant + Rooting + Sprouting + Starts Flowering; T6: Before Transplant + Rooting + Sprouting + Starts Flowering+ Starts Fruiting; T7: Rooting; T8: Rooting + Sprouting; T9: Rooting + Sprouting + Ínicio do Florescimento; T10: Rooting + Sprouting + Starts Flowering+ Starts Fruiting; T11: Sprouting (mesmo dia); T12: Sprouting + Starts Flowering; T13: Sprouting + Starts Flowering+ Starts Fruiting; T14: Starts Flowering; T15: Starts Flowering+ Starts Fruiting; T16: Starts Fruiting. The second experiment was conducted ...